Houses of worship distribution pattern in Surakarta City and its influencing factors - Dhenisa Gitviana Putri; Choirul Amin (Universitas Negeri Malang, 2022)
The purpose of this study is to determine the pattern of worship places distribution in Surakarta City and its influencing factors. This study used observation and field survey methods. The data analysis was carried out using the Average Nearest Neighbor (ANN) with a total of 145 points of worship, while the selected factors consisted of demographic factors and road networks. These two factors were chosen because the construction of places of worship was more influenced by the number of residents and the ease of accessibility to these places of worship. The results of this study indicate that the mosque has a clustered pattern, while churches, pagodas, and temples have the same dispersed pattern. Demographic factors carry no sufficient effects on the existence of places of worship because they are not proportional to the population density and number of places of worship. These results are expected to support demographic learning of the religion adopted by the population. The road network factor at places of worship is more influenced by collector roads because of its ease of accessibility compared to arterial roads.